A hybrid approach to online game matchmaking using Las Vegas algorithm and K-nearest neighbor - Angela Mariz R. Chavez, Marck England P. Bautista. 4 0 16; 5 (2023)
u
Undergraduate Thesis: (Bachelor of Science in Information Technology), Pamantasan ng Lungsod ng Maynila, 2023.
Keywords: 2 -- 0; 6; 20; 20; 2